Impact on Clinical Decision Making of Next-Generation Sequencing in Pediatric Epilepsy in a Tertiary Epilepsy Referral Center. (January 2020) - Hoelz, Hannes; Herdl, Christian; Gerstl, Lucia; Tacke, Moritz; Vill, Katharina; von Stuelpnagel, Celina; Rost, Imma; Hoertnagel, Konstanze; Abicht, Angela; Hollizeck, Sebastian; Larsen, Line H. G.; Borggraefe, Ingo
Background . Next-generation sequencing (NGS) describes new powerful techniques of nucleic acid analysis, which allow not only disease gene identification diagnostics but also applications for transcriptome/methylation analysis and meta-genomics. NGS helps identify many monogenic epilepsy syndromes. Pediatric epilepsy patients can be tested using NGS epilepsy panels to diagnose them, thereby influencing treatment choices. The primary objective of this study was to evaluate the impact of genetic testing on clinical decision making in pediatric epilepsy patients. Methods . We completed a single-center retrospective cohort study of 91 patients (43 male) aged 19 years or less undergoing NGS with epilepsy panels differing in size ranging from 5 to 434 genes from October 2013 to September 2017. Results . During a mean time of 3.6 years between symptom onset and genetic testing, subjects most frequently showed epileptic encephalopathy (40%), focal epilepsy (33%), and generalized epilepsy (18%). In 16 patients (18% of the study population), "pathogenic" or "likely pathogenic" results according to ACMG criteria were found. Ten of the 16 patients (63%) experienced changes in clinical management regarding their medication and avoidance of further diagnostic evaluation, that is, presurgical evaluation. Conclusion . NGS epilepsy panels contribute to the diagnosis of pediatric epilepsy patients and may change their clinical management with regard to both preventing unnecessary and potentially harmful diagnostic procedures and management. Thus, the present data support the early implementation in order to adopt clinical management in selected cases and prevent further invasive investigations. Given the relatively small sample size and heterogeneous panels a larger prospective study with more homogeneous panels would be helpful to further determine the impact of NGS on clinical decision making.